Revealing consumer preferences by observing information search - Caspar G. Chorus; Harry J. P. Timmerman (Journal of Choice Modelling, 2008)
Motivated by the notion that consumers' use of the internet creates a wealth of data on information search, we put forward the idea that observed information searches may be used for deriving consumer preferences. First, we derive a theoretical model of consumer behaviour under uncertainty and information availability. In theory, this model provides the opportunity to derive consumer preferences from information search alone. The model is then illustrated, based on an articial dataset. Estimation results show that information search concerning an uncertain attribute of a good can indeed be used to identify consumer preferences concerning the good. Although the proposed model relies on a number of assumptions (for example the premises behind expected utility maximisation) we show how these can be relaxed without compromising the potential of the approach in general.
Keywords: 330; information search; consumer preferences; choice-modelling